(3JWhQg (B- (3eagheg (B- (3GSJNOGeg eY GdfGTFIs - (3OQhjT Rcj eMeOs ((3GdbGgQIs (3OGQ GdacQ GdYQHjs, 1997)
(3GdJOQjH GdHdjheJQi CMOK hSGFd GdJOQjH GdQjGVj GdJj JYed Ydi GdGQJbGA HGdbOQGJ GdHOfjI h NGUI aj GdQjGVjGJ h GdCdYGH GdJj JJWdH GdbhI GdeejRI HGdSQYI ShGA aj GdhKH h GdbaR Chaj GdQej hGdOaY(B.s
Keywords: (3GdJOQjH GdQjGVjs